A prospective study of serum electrolyte disorders and their clinical manifestation in HIV patients - Damor, Ajesh Kumar; Honta, Praful Bala (International Journal of Research in Medical Sciences, 2018)
Background: Present study was conducted to evaluate the serum electrolyte disorders and their clinical manifestation in HIV positive patients. Methods: Total 100 patients who were known to be HIV positive or those who were found to be HIV positive were taken. HIV infection was diagnosed by one ELISA and two E/R/S test. All clinical diagnosis medication and routine chemical profiles were recorded along with detailed history and physical examination. Fluid depletion was inferred from the findings like decreased skin turgor, dry mucus membrane; fluid overload was ascertained by presence of jugular venous distension and dependent pulmonary rales. Hyponatremia was defined as a serum sodium concentration less than 135mmol/L and hypokalemia was defined as potassium concentration less than 3.5mmol/L. Results: Eighty percent patients had disorders of electrolyte imbalance. Most common electrolyte was hyponatremia (58%) and hypokalemia (28%). The mean serum sodium concentration was 133.48±7.06 and potassium concentration was 3.87±0.63. Neuromuscular manifestation and neuropsychiatric manifestation were present in 58% and 49% respectively. Conclusions: Patients with HIV infection may develop a bewildering variety of electrolyte and acid-base disturbances. Hyponatremia and hypokalemia from many causes is common and associated with an increased mortality.